FLUKTUASI KOMUNITAS FITOPLANKTON DI WADUK MALAHAYU, BREBES, JAWA TENGAH - MULYADI MULYADI (BERITA BIOLOGI, 1985)
MULYADI.1985. Phytoplankton community of Malahayu reservoir,Brebes,Central Java. Berita Biologi 3 (3) : 91 - 94. This study was carried out from July to October 1982, and a number ol 23 genera of phytoplankton was recorded.The population of Chlorophyceae was found to be the highest.The highest density of the phytoplankton community was recorded in September while the lowest density in August. The distribution of ftiytoplanktons in five stations was found to be relatively equal.